2017
DOI: 10.1371/journal.pone.0172753
|View full text |Cite
|
Sign up to set email alerts
|

Affordability of medicines in the European Union

Abstract: BackgroundMedications and their prices are key issues for healthcare. Although access to medicines at affordable prices had been specified as a key objective of the European Health Policy, it seems that these goals have not been achieved. Therefore, we attempted an evaluation of affordability of selected medicines at full prices.MethodsThe analysis concerned 2012 and was conducted between 2013 and 2015 in all the European Union (EU) countries divided into 3 groups depending on the date of their accession to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…While differences in methodology (different baskets of medicines surveyed, different time lines) of the MeTA survey and this research limit comparability, both studies concluded that parts of outpatient medicines were unaffordable for the Kyrgyz population in 2015. Unaffordability of essential medicines is a barrier to access to medicines in many countries worldwide [76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…While differences in methodology (different baskets of medicines surveyed, different time lines) of the MeTA survey and this research limit comparability, both studies concluded that parts of outpatient medicines were unaffordable for the Kyrgyz population in 2015. Unaffordability of essential medicines is a barrier to access to medicines in many countries worldwide [76][77][78][79][80].…”
Section: Discussionmentioning
confidence: 99%
“…Although it seems easy to connect the e-mail with the pharmacy's location, it was not our aim to collect and then present such data. We would not be accused of pharmacy advertising, which is strictly forbidden in Poland [5].…”
Section: Methodsmentioning
confidence: 99%
“…It might be easy to connect the completed questionnaire with the e-mail address of the pharmacy, but it was not our aim to collect and then to present these data. It could be considered as a pharmacy advertising which is strictly forbidden in Poland (15).…”
Section: Methodsmentioning
confidence: 99%